Покращення метрологічних характеристик портативних частотних аналізаторів імпедансу - Хома, Юрій Володимирович (Національний університет "Львівська політехніка", 2014)
Дисертаційна робота присвячена вирішенню важливої науково-прикладної задачі – підвищенню точності і розширенню частотного діапазону портативних частотних аналізаторів імпедансу (ЧАІ). В роботі сформульовано вимоги до портативних ЧАІ та розроблено концепцію покращення їх метрологічних характеристик, яка ґрунтується на мінімізації аналогової частини вимірювального каналу і передбачає застосування цифрового опрацювання сигналів і алгоритмічної корекції для компенсації похибок результатів вимірювання. Обґрунтовано доцільність модифікації структури DDS-синтезаторів для формування зондувального і ортогональних сигналів ЧАІ, встановлено вимоги до їх параметрів і досліджено джерела похибок. Проаналізовано особливості реалізації квадратурного розділення за алгоритмом одночастотного перетворення Фур’є, одержано моделі похибок, на основі яких обґрунтовано шляхи підвищення точності ЧАІ. Показано переваги застосування у структурі портативних ЧАІ виносних активних вимірювальних перетворювачів. Розроблено математичні моделі перетворювачів імпедансу і адмітансу в напругу, на основі яких синтезовано аналітичні вирази для компенсації частотних похибок. Створено метрологічну модель вимірювального каналу розроблених ЧАІ, описано і проаналізовано варіанти їх побудови на сучасній елементній базі. Диссертационная работа посвящена решению важной научно-прикладной задачи – повышению точности и расширению частотного диапазона портативных частотных анализаторов импеданса (ЧАИ). В работе сформулированы требования к портативным частотным анализаторам импеданса и разработана концепция улучшения их метрологических характеристик, основанная на минимизации аналоговой части измерительного канала и применении цифровой обработки сигналов и алгоритмической коррекции для компенсации погрешностей результатов измерения. Обоснована целесообразность модификации структуры DDS-синтезаторов для формирования зондирующего и ортогональных сигналов ЧАИ, установлены требования к его параметрам и исследованы источники погрешностей. Проанализированы особенности реализации квадратурного преобразования по алгоритму одночастотного преобразования Фурье, получены модели погрешностей, что позволило предложить пути повышения точности ЧАИ. Обоснованы преимущества применения в структуре портативных ЧАИ выносных активных измерительных преобразователей. Разработаны математические модели преобразователей импеданса и адмитанса в напряжение, на основании которых синтезированы аналитические выражения для компенсации частотных погрешностей. Создана метрологическая модель измерительного канала разработанных ЧАИ, описаны и проанализированы варианты их построения на современной элементной базе. The thesis is devoted to solve actual applied scientific task –improvement of accuracy as well as extension of frequency band of portable impedance analyzers. Requirements on the properties of portable impedance analyzers have been formulated and a novel concept of improvement of their metrological characteristics has been developed in the paper. This concept is based on the idea of minimizing of the analog part of the impedance analyzers’ measuring channel as well as errors compensation using algorithmic correction and digital signal processing. In the thesis has been proved that using means of direct digital synthesis for probe and orthogonal signals generation in portable impedance analyzers makes a lot of sense. Existing types of direct digital synthesizers have a various disadvantages that make problematic their application as signal source in impedance spectroscopy. Therefore a new modified structure of direct digital synthesizers based on combination of binary counter and phase accumulator has been proposed. Errors and spectral composition of this modified synthesizer have been investigated and requirements to its parameters have been determined. Advantages and disadvantages of quadrature conversion based on the algorithm of single-point Fourier transform have been analyzed. Mathematical models of errors of Fourier transform errors caused by harmonic distortion and spectral leakage have been developed. These models were used to improve quadrature conversion precision. Advantages of application of active measurement converters in measuring channel of portable impedance analyzers have been show in the paper. This approach allows to reach high accuracy and resolution, good dynamic characteristics, stable current and voltage conditions on the object under test as well as simple (one-channel) structure, small dimensions, weight and power consumption. Formalized mathematical models of active measurement impedance/admittance-to-voltage converters were developed. Using these models analytical equations for algorithmic correction of measurement results were synthesized. Application of algorithmic correction enables elimination of frequency errors of analog devices. Metrological model of measuring channel of designed portable impedance analyzers has been developed. Three design options using ASIC (application-specific integrated circuit), DSC (digital signal controllers) and FPGA (field-programmable gate array) have been described and analyzed. The results of the work can be used in various applications, such as qualimetry (control of impurities) and electrochemical analysis (tomography), impedometric sensors (proximity detection) and the resonance systems (quartz thermometers), PLL devices (not contact AFM) and signal processing (FFT error compensation).
Улучшение метрологических характеристик портативных частотных анализаторов импеданса
Improvement of metrological characteristics of portable impedance frequency analyzers
Keywords: імпеданс; адмітанс; спектроскопія; частотні аналізатори імпедансу; метрологічна модель; прямий цифровий синтез; квадратурне розділення; одночастотне перетворення Фур’є; перетікання спектру; віконне згладжування; алгоритмічна корекція; частотна похибка; импеданс; адмитанс; спектроскопия; частотные анализаторы импеданса; метрологическая модель; прямой цифровой синтез; квадратурное преобразование; одночастотное преобразование Фурье; растекание спектра; оконное сглаживание; алгоритмическая коррекция; частотная погрешность; impedance; admittance; spectroscopy; impedance frequency analyzer; metrological model; direct digital synthesis; quadrature conversion; single-point Fourier transform; spectral leakage; window functions (windowing); algorithmic correction; frequency errors